Memahami Dialektika Antara Perilaku Agama dan Politik dalam Perumusan Hukum Islam di Indonesia - Syahbudi, S. (AL-ISTINBATH : Jurnal Hukum Islam, 2021)
This study aims to explain the formulation of Islamic law is a product of the dialectic between political and religious behavior. Dialectics is often related to relations and power as well as interactions and connections. This article uses a qualitative method with descriptive analysis that compares several literatures by describing the relationship between religious and political dialectics in the formulation of Islamic law. Furthermore, this article uses an inclusive and exclusive theoretical framework. The essence of this theoretical framework is the awareness of the recognition of the existence of salvation beyond self-belief. This article argues that religious doctrines influence the political behavior will tend to produce an inclusive attitude, but political behavior affects the religion will lead to produce an exclusive behavior in formulating of Islamic law. An inclusive attitude can be seen from the openness in responding to political changes by using generally accepted opinion trends. Meanwhile, this exclusive attitude can be seen from the tendency to use legal terms such as lawful, unlawful, infidel or apostasy which applies specifically. However, both inclusive and exclusive models are expressions in the formulation of Islamic law. The conclusion is that the dialectic between political and religious behavior has implications for the recognition of legal pluralism as a dynamic character of Islamic law.